2015
DOI: 10.1186/s40317-015-0079-y
|View full text |Cite
|
Sign up to set email alerts
|

Application of a computer vision technique to animal-borne video data: extraction of head movement to understand sea turtles’ visual assessment of surroundings

Abstract: Background: An animal-borne video recording system has recently been developed to study the behavior of freeranging animals. In contrast to other types of sensor data (i.e., acceleration), video images offer the advantage of directly acquiring information without analysis. However, most previous findings have only been obtained through visual observation of image data. Here, we demonstrate a new method of data analysis for animal-borne videos using a computer vision technique referred to as template matching. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Video recording observations combined with collection of GPS data improves the collection of precise data, both for identifying the species involved and for determining location and circumstances of the collisions (train speed, bird behavior, etc.). Techniques like video recording from fixed points, vehicles, or animal-borne cameras have been applied to study animal behavior and monitor wildlife (Whorff and Griffing, 1992;Thompson et al, 1999;Okuyama et al, 2015), but rarely to assess mortality risk (Desholm et al, 2006;Cryan et al, 2014;Furness, 2014;Doppler et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Video recording observations combined with collection of GPS data improves the collection of precise data, both for identifying the species involved and for determining location and circumstances of the collisions (train speed, bird behavior, etc.). Techniques like video recording from fixed points, vehicles, or animal-borne cameras have been applied to study animal behavior and monitor wildlife (Whorff and Griffing, 1992;Thompson et al, 1999;Okuyama et al, 2015), but rarely to assess mortality risk (Desholm et al, 2006;Cryan et al, 2014;Furness, 2014;Doppler et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in the present preliminary study, we utilized a behavioral observation method by attaching a wearable camera to calves. Several studies have reported their application in goats [ 29 ] and sea turtles [ 30 ], but there is no study on the daily behavioral time budgets. The camera was chosen based on its small size and its ability to be worn on the animal’s body.…”
Section: Introductionmentioning
confidence: 99%
“…Two notable examples include the use of object tracking on the prey of falcons and template matching to determine the head position of sea turtles, though in both cases using 2D images [13,14].…”
Section: Introductionmentioning
confidence: 99%